Employment of foreign labour in plantation industry: the case study on Tai Tak company / Siti Aminah Osman - Osman, Siti Aminah (2010)
This study investigates on the employment of foreign labour in the plantation industry. Malaysia as the country’s that having a high rate on foreign labour in total plantation labour force which is the oil palm sector has the highest number at about 577,900 workers comprising some 350,000 foreigners. The problem is compounded by the fact that it is difficult to get local workers. The purpose of this research are mainly focus on the factor influence foreign labour in the plantation, the impact by hiring foreign labour and also potential opportunity to reduce cost by hiring foreign labour. This study is done by using an interview method and secondary data to find a solution regarding this issue. From the information obtained, there are few factor influence employment of foreign labour are to fill up vacancies and cheap workforce. Beside, they are more committed to do their work rather than local worker who like to absent during a work time. However, there is also an impact by hire foreign worker such as bring in social problem in the workplace and also take a long time to process their permit. Regardless that, there is also a few benefits by hire foreign labour because it helps to reduce labour cost and increase the production activity. This is due to foreign worker are paying lower than local labour and they also didn’t receive any compensation benefit that company need to pay for it. So it can maximize the profit for the company and increase the production. Therefore, from the findings it can be conclude that foreign worker are cheaper and committed to their work because they eager to send money to their home country. By conducting this study, the researcher hope the result and some of the recommendations can help the industry to improve its condition and attract more local to work in plantation sector.